Effect of optimal neoadjuvant chemotherapy on oncological outcomes of locally advanced bladder cancer with laparoscopic radical cystectomy: A matched‐pair analysis in a multicenter cohort. (7th March 2021) - Kubota, Masashi; Kanno, Toru; Inoue, Takahiro; Yamasaki, Toshinari; Okumura, Kazuhiro; Ito, Katsuhiro; Yamada, Hitoshi; Fujii, Masato; Shimizu, Yosuke; Yatsuda, Junji; Moroi, Seiji; Shichiri, Yasumasa; et al.
Abstract : Objectives: To assess the effect of optimal neoadjuvant chemotherapy of at least three cycles of cisplatin‐based regimen on oncological outcomes of clinical stage T3 or higher bladder cancer treated with laparoscopic radical cystectomy. Methods: Laparoscopic radical cystectomies carried out at 10 institutions were included in this retrospective study. The outcomes of patients who received optimal neoadjuvant chemotherapy and those who did not receive neoadjuvant chemotherapy were compared using propensity score matching in clinical stage T3–4 or T2 cohorts, separately. Results: Of the 455 patients screened, matched pairs of 54 patients in the clinical T3–4 cohort and 68 patients in the clinical T2 cohort were finally analyzed. In the cT3–4 cohort, the 5‐year overall survival (78% vs 41%; P  = 0.014), cancer‐specific survival (81% vs 44%; P  = 0.008) and recurrence‐free survival (71% vs 53%; P  = 0.049) were significantly higher in the optimal neoadjuvant chemotherapy group than in the no neoadjuvant chemotherapy group; no significant survival difference was shown between the two groups in the cT2 cohort. In the cT3–4 cohort, the incidence of local recurrence (4% vs 26%; P  = 0.025) and abdominal or intrapelvic recurrence, including peritoneal carcinomatosis (7% vs 30%; P  = 0.038), was significantly lower in the optimal neoadjuvant chemotherapy group. Conclusions: Administration of optimal neoadjuvant chemotherapy has a significant survival benefit. It decreases the incidence of local and atypical recurrence patterns in patients with clinical stage T3 or higher locally advanced bladder cancer undergoing laparoscopic radical cystectomy.